Climate Change and Food Security in Selected SADC Countries: A Feasible Generalized Least Squares Approach - Matsvai, Simion; Podzo, Fradreck; Hosu, Yiseyon S. (International Journal of Economics and Financial Issues, 2025)
Climate change poses a significant threat to the attainment of the sustainable development goals (SDGs) and directly affects food security in SADC countries, as it negatively impacts agricultural production, which is a primary source of livelihood. The study examined the impact of climate change and climate variability (rainfall amount, temperature, and carbon emissions) on food security in the SADC region based on 14 countries of the 16 SADC members states. Secondary data for the period 1990 to 2023 was used. Data analysis was conducted using Feasible Generalized Least Squares (FGLS). The results revealed that extreme temperatures and excessive or poor rainfall had a significant negative impact on food security (food availability and food accessibility) both in the short run and in the long run. Rainfall had a significant positive effect on food security (food availability, accessibility, and utilization) in the long run. Lastly, CO2 emissions positively impacted food availability and accessibility but did not affect food utilization. The study recommended increasing climate change education and training programs to nationals regarding climate change and variability to ensure the adoption of innovative, adaptive and sustainable agriculture strategies such as SMART agriculture complemented by paving way for humanitarian interventions and Non-Governmental Organizations targeting humanitarian, climate change adaptation and climate change mitigation strategies for farmers. Nations should also direct a significant proportion of their budgets towards climate action (climate finance) to speed up the adaptation and mitigation strategies.